2016
DOI: 10.5505/tjtes.2016.70137
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Subacute and Chronic Period Sleep Quality in burns patient

Abstract: AMAÇ:Bu araştırmanın amacı yanık hastasında sub akut ve kronik dönemde uyku kalitesinin belirlenmesidir. GEREÇ VE YÖNTEM:Araştırma, bir üniversite hastanesinde Ocak 2014-Haziran 2015 tarihleri arasında tanımlayıcı olarak yapıl-mıştır. Araştırmaya 36 hasta dâhil edilmiştir. Verilerin toplanmasında hastaların tanıtıcı özelliklerini belirleyen form ve Pittsburgh Uyku Kalitesi İndeksi (PUKİ) kullanılmıştır. Araştırmadan elde edilen verilerin analizi için SSPS 22.0 paket programı kullanılmış olup tüm analizlerde is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Burn injury is one of the longest traumas based on the duration of both hospitalisation and rehabilitation periods and its role in causing severe mortality and morbidity. [1] The American Burn Association (ABA) defines major burns as second degree burns with a total body surface area (TBSA) greater than 25% in adults, second degree burns with TBSA greater than 20% in children and all third-degree burns with TBSA above 10%. All burns, including hands, face, eyes, ears, feet, perineal burns, inhalation burns, electrical burns and fractures, fall into the major burn category.…”
Section: Introductionmentioning
confidence: 99%
“…Burn injury is one of the longest traumas based on the duration of both hospitalisation and rehabilitation periods and its role in causing severe mortality and morbidity. [1] The American Burn Association (ABA) defines major burns as second degree burns with a total body surface area (TBSA) greater than 25% in adults, second degree burns with TBSA greater than 20% in children and all third-degree burns with TBSA above 10%. All burns, including hands, face, eyes, ears, feet, perineal burns, inhalation burns, electrical burns and fractures, fall into the major burn category.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders in burn patients have become a widespread concern, and steps are being taken to address their sleep deprivation [ 10 , 11 ]. A study revealed that more than 85% burn patients had trouble sleeping throughout their treatment [ 12 ]. Problems such as increased pain, anxiety, and pruritus can lead to insomnia among burn patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%